2014
DOI: 10.1007/s13277-014-2638-x
|View full text |Cite
|
Sign up to set email alerts
|

α2,6-linked sialic acids on N-glycans modulate the adhesion of hepatocarcinoma cells to lymph nodes

Abstract: The alterations of cell surface sialylation play a key role in tumor metastasis. Enhanced α2,6-sialylation on N-glycans results from overexpression of the sialyltransferase ST6Gal-I. Hca-F and Hca-P cells are murine hepatocarcinoma cell lines which metastasize only to the lymph nodes. Our previous study revealed that ST6Gal-I was involved in the adhesion of Hca-F cells to fibronectin. However, the roles of sialic acids in the adhesion of Hca-F cells to lymph nodes still remain poorly understood. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…16 To inhibit ST6Gal-I expression, MHCC97-H cells were transfected with shRNA sequences targeting ST6Gal-I and a negative control vector (shNC) was constructed as described previously. 16, 24 These cells were transfected with a mixture of plasmids and Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) depending on the manufacturer’s instructions. To select stably transfected cells, the culture medium was replaced with complete medium containing 800 mg/ml of G418 (Sigma-Aldrich, Darmstadt, Germany) after 48 h. Modified expression was confirmed by qPCR and western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 To inhibit ST6Gal-I expression, MHCC97-H cells were transfected with shRNA sequences targeting ST6Gal-I and a negative control vector (shNC) was constructed as described previously. 16, 24 These cells were transfected with a mixture of plasmids and Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) depending on the manufacturer’s instructions. To select stably transfected cells, the culture medium was replaced with complete medium containing 800 mg/ml of G418 (Sigma-Aldrich, Darmstadt, Germany) after 48 h. Modified expression was confirmed by qPCR and western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…22, 23 In our previous study, we found that upregulation of ST6Gal-I increased the adhesive capability of mouse hepatocarcinoma cell to lymph node. 24 However, the predictive and prognostic values of ST6Gal-I and its effect on HCC progression remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ST6Gal-I is known to be highly expressed in multiple types of cancer, including colorectal, ovarian, oral, breast, epithelial and liver carcinomas [611], and its expression has been positively correlated with adhesion, invasion and metastasis in tumor cells [12–14]. Recently it has been reported that ST6Gal-I mediates the sialylation of tumor-necrosis factor receptor-1 (TNFR1) and Fas receptors to inhibit cell apoptosis, and plays a vital role in resistance to cisplatin-induced apoptosis of ovarian cancer [15, 16, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have devoted much attention to the biological functions of protein α-2, 6-sialylation, but the regulatory mechanisms controlling sialylation levels are poorly understood2122. Eukaryotic cells need to maintain a sialylation steady state, because hypersialylation may result in cell dysfunction.…”
mentioning
confidence: 99%